1999
DOI: 10.1164/ajrccm.160.1.9811006
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Sputum Mycobacterium tuberculosis Messenger RNA as a Surrogate for Response to Chemotherapy

Abstract: Effective treatment regimens for pulmonary tuberculosis are difficult to assess because of the slow growth rate of Mycobacterium tuberculosis in culture and its protracted clearance from sputum. A rapid method that reflects effective antimicrobial activity would markedly advance evaluation of treatment and promote the assessment of new antituberculosis drugs. Conventional methods measure the progressive reduction of numbers of acid-fast bacilli in the sputum smear and the clearance of organisms in sputum cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(89 citation statements)
references
References 32 publications
3
86
0
Order By: Relevance
“…More recently, the emergence of molecular medicine has resulted in the increased use of techniques able to quantitate levels of RNA in clinical diagnostics. Such applications are wide-ranging and include procedures designed to quantify the regulation and expression of drug resistance markers in tumour cells (Ramachandran & Melnick 1999), monitor responses to chemotherapy (Desjardin et al 1999), measure the biodistribution and of transcription of geneencoded therapeutics (Fairman et al 1999), provide a molecular assessment of tumour stage (Bustin & Dorudi 1998), detect circulating tumour cells in cancer patients (Ghossein & Rosai 1996), and detect bacterial (Hill 1996) and viral (Holodniy 1994) pathogens.…”
Section: Why Mrna Quantification?mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the emergence of molecular medicine has resulted in the increased use of techniques able to quantitate levels of RNA in clinical diagnostics. Such applications are wide-ranging and include procedures designed to quantify the regulation and expression of drug resistance markers in tumour cells (Ramachandran & Melnick 1999), monitor responses to chemotherapy (Desjardin et al 1999), measure the biodistribution and of transcription of geneencoded therapeutics (Fairman et al 1999), provide a molecular assessment of tumour stage (Bustin & Dorudi 1998), detect circulating tumour cells in cancer patients (Ghossein & Rosai 1996), and detect bacterial (Hill 1996) and viral (Holodniy 1994) pathogens.…”
Section: Why Mrna Quantification?mentioning
confidence: 99%
“…Similarly, the calcium ionophore A23187 induces GAPDH transcription through specific motifs in its promoter (Chao et al 1990). Growth hormone (Freyschuss et al 1994), vitamin D (Desprez et al 1992), oxidative stress (Ito et al 1996), hypoxia (Graven et al 1994, Zhong & Simons 1999, manganese (Hazell et al 1999) and the tumour suppressor TP53 (Chen et al 1999), have all been shown to activate its transcription, which is also inducible in endothelial cells (Rimarachin et al 1992) and during apoptosis (Ishitani et al 1997). Furthermore, it has been shown to be upregulated in cancer -for example in rat hepatomas (Chang et al 1998), malignant murine cell lines (Bhatia et al 1994) and human prostate carcinoma (Ripple & Wilding 1995).…”
Section: Gapdhmentioning
confidence: 99%
“…These sequences were as follows: RT primer (-266RT) 5¢-gcgtgtgctcgtcg-3¢; Forward primer (160F) 5¢-gcggtggtccgtttgga-3¢; Reverse primer (227R) 5¢-ccagggtcaagctcgacgtt-3¢; Probe (181T) 5¢-FAMcccggcattgacgtcgacaagg-3¢TAMRA. Sequences used to detect M. tuberculosis acr1 and 16S were as described previously (Desjardin et al, 1999;2001). All probes were dually labelled with 5 carbofluorescein (FAM) at the 5¢ end and N,N,N¢,N¢-tetramethyl-6-carborhodamine (TAMRA) at the 3¢ end.…”
Section: Resistance To Hydrogen Peroxidementioning
confidence: 99%
“…Applications of real-time RT-PCR include quantifying the regulation and expression of drug resistance markers in tumor cells (Ramachandran and Melnick, 1999), monitoring responses to chemotherapy (Desjardin, Perkins, Wolski, et. al, 1999), providing a molecular assessment of tumor stage (Bustin and Dorudi, 1998), detecting circulating tumor cells in cancer patients (Ghossein and Rosai, 1996), and detecting bacterial (Hill, 1996) and viral (Holodniy, 1994) pathogens including HIV (Connor et al…”
Section: 3b Gene Expression (Mrna Quantification)mentioning
confidence: 99%